Designation of modern management in education - Šormaz Goran; Anđelić Slavica; Marković-Blagojević Marija (Trendovi u Poslovanju)
Management, as a phenomenon of a developed society, is analyzed and perfected in conditions of growing globalization, in a world filled with challenges to find answers. Economic development depends on the functioning of management and managers in all sectors of human activity, as well as the overall social and economic development of a country. Today, special attention is given to the coordination of the theory and practice of the management of the countries in transition. The scientific approach to management in the field of education involves functional coherence and interconnection of human and material resources in order to achieve the tasks of individuals and the system of Change, which requires modern access to management in education, requires greater managerial activities in all spheres of life, so that the education system could make it more efficient and effective. Education in Serbia has to go through the changes that have already taken place in the developed countries, because we live in a society of knowledge and economy of knowledge. Education represents the "central nervous system" of every society - the pedagogic, educational, cultural chain that constantly vibrates. In this chain, a significant link, in addition to educators, teachers, professors and others, should be an educated and skilled manager. It is widely known that managers are required to possess the capacity for innovation and management in the planning, organization, coordination and control of the performance of educational institutions.